Power grid classification through Electrical Network Frequency - Zaman, MD.Arif Uz; Mortoza, Tasnim; Abid, Zawad Hasan; Musa, MD. Abu (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.